1. The problem statement, all variables and given/known data given z=yf(x^2-y^2) show that the x(∂z/∂y)+y(∂z/∂x)=xz/y 3. The attempt at a solution cut it short, my ∂z/∂y= f(x^2-y^2)-2(y^2)f(x^2-y^2) ∂z/∂x=2xyf(x^2-y^2) i was able to prove that x(∂z/∂y)+y(∂z/∂x)=xz/y But i need help with partial differentiations when they give an equation like z=f(x^2-y^2) I've read about partially differentiating such equations somewhere before. Can someone please check if i am doing it right? Also, what is this kind of partial differentiation called? (such as partially differentiating z=f(x^2-y^2) I would really appreciate if someone could tell me what is it called so i could read up more about it and do more examples of this kind.